Book Reviews - Wagner, Kristen Anderson and Berra, John and Riley, John A and Douglas, Paul (Film International, 2010)
Douglas Fairbanks, Jeffrey Vance, with Tony Maietta , (2008) Berkeley: University of California Press and Los Angeles: Academy of Motion Picture Arts and Sciences, 368 pp., ISBN 9780520256675 (hbk), $45.00 Remade in Hollywood: The Global Presence in Transnational Cinemas , Kenneth Chan , (2009) Hong Kong: Hong Kong University Press, 259 pp., ISBN 9789622090569 (pbk), $27.95, ISBN 9789622090552 (hbk), $57.50 Hong Kong Cinema Since 1997: The Post-Nostalgic Imagination , Vivian P.Y. Lee , (2009) Basingstoke: Palgrave Macmillan, 256 pp., ISBN 9780230221437 (hbk), $85.00 Translating Time: Cinema, the Fantastic, and Temporal Critique , Bliss Cua Lim , (2009) Durham, NC: Duke University Press, 345 pp., ISBN 9780822345107 (pbk), $23.95 Postcolonial African Cinema: From Political Engagement to Postmodernism , Kenneth W. Harrow , (2007) Bloomington: Indiana University Press, 296 pp., ISBN 9780253219145 (pbk), $25.95
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9maWluLjguNS44Mg